Eastern Caribbean Currency Union : Selected Issues Paper. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2019)
This Selected Issues paper presents a quantification of the long-term benefits of ex-ante resilient investment and insurance needs against natural disasters (ND) in Eastern Caribbean Currency Union (ECCU). Cost-benefit analysis of resilient investment based on a dynamic stochastic general equilibrium model tailored to small states and calibrated to all ECCU economies is also discussed in the paper. The model's aggregate production function illustrates the interaction among the participating sectors and their contribution to output, ultimately informing the role of resilient investment. The study also quantifies government insurance coverage needs and costs using an empirical stochastic model that simulates NDs fiscal costs. The insurance needs are framed within the World Bank insurance layering framework. The results in this paper underscore the importance of a shift from ex-post recovery to a focus on ex-ante resilience building. Ex-ante resilient investment and insurance are key to the welfare and financial sustainability of the ECCU, given high intensity and recurrence of NDs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet